Contact allergy in children with atopic dermatitis - Bartoszak, Leszek; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Atopic dermatitis (AD) is one of the most common skin diseases in children. It is a chronic and recurrent disease involving the epidermis and dermis. It is highly pruritic and skin lesions present typical eczematous morphology as well as characteristic localizations. AD is often associated with other atopic diseases. Allergic contact dermatitis (ACD), like AD, is an eczematous disease. However, it is mediated through immune mechanisms different from those of AD. ACD is a skin disorder that occurs at sites of contact with small chemical haptens in only those individuals who have been previously exposed to, and immunologically sensitized to, a particular chemical. Despite different etiologies, AD and contact dermatitis have been the focus of many studies examining the potential association of the two conditions. In the past it was believed that patients suffering from AD were less likely to suffer from ACD. Previously it was also common to believe that ACD was rare in children. However, recent studies demonstrate that the frequency of contact allergies in the course of AD, and also the frequency of contact allergies in children, is underestimated in general. This article presents current views on the clinical and immunological association of AD and ACD in children.